THU0115 Disability (HAQ) and quality of life (SF-12) as related to adherence and health literacy in patients with rheumatoid arthritis. (15th June 2017) - Kuipers, JG; Koller, M; Zeman, F; Mueller, K; Rueffer, JU
Abstract : Background: Disabilities in daily living and quality of life are key endpoints to evaluate the outcome of treatment for rheumatoid arthritis (RA). Among factors that may contribute to good outcome are adherence (i.e., the extent to which patients' behaviors corresponds with agreed recommendations from their doctor) and health literacy (patients' understanding and use of health information). Objectives: The survey included a representative, nationwide sample of German physicians specialized in RA and patients with RA. The physician questionnaire included the disease activity score (DAS28) and medical prescriptions. The patient questionnaire included fatigue (EORTC QLQ-FA13), health assessment questionnaire (HAQ), quality of life (SF-12), health education literacy (HELP), and patients' listings of their medications. Methods: Adherence was operationalized in various ways: patient-reported (CQR5), behavioral (correspondence between physicians and patients listings of medications), physician-assessed (five-point rating scale ranging from 1=very adherent to 5=not at all adherent) and a combined measure of physician rating (1= very adherent, 0 = less adherent) and the match between physicians' prescriptions and patients' accounts of their medications (1 = perfect match, 0 = no perfect match), leading to three categories of adherence: high, medium and low. Linear regressions were calculated using HAQ and SF-12 (physical and psychological) as dependent variables and adherence, health literacy and the set of demographic and clinical variables as predictor variables. Results: A total of 708 pairs of patient and physician questionnaires were analyzed. The mean age of the patients, of whom 73% were women, was 60 years (SD=12). Multiple regression analyses show, that health literacy is an independent predictor for HAQ and both SF-12 scales. Adherence by doctor is an independent predictor for both SF-12 scales while the adherence composite score is an independent predictor for HAQ and SF-12 psychological. Taking all 4 rheumatoid medications as prescribed is an independent predictor for HAQ and SF-12 physical. All models are additionally controlled for age, sex, smoking (y/n), drinking alcohol (y/n), sport (y/n). Conclusions: This study showed that HAQ and SF-12 were related to adherence and health literacy. This finding highlights the importance of patient education and counseling in order to increase both, medical understanding and adherence to therapy. Acknowledgements: The TRACE-Study was sponsored by an unrestricted grant from Chugai. Disclosure of Interest: None declared